(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Making use of a known but not sufficiently explored serial source, such as the dispatches (dispacci) of the venetian rectors of Padua for the years 1602-1630, the period of important breakages of the banks and the flooding of rivers, we intend to propose the examination of this case study to trasport the naural disaster into field of social and economic history. The quick comparison with the documentation of other podesterias (Verona, Vicenza and Chioggia) for the fatal year of 1608 allows us to grasp the rapresentativeness of the historical period. In that year in Padua the supply crisis emerges in the contradictions in city and country relations and in the recurrence of social tensions. The picture is bleak: a main communication waye such as the road Mestrina is transformed into colander by the waters. ‘Deluge’ of snow accumulates in the city which become cumbersome scourges for the venetian rapprentatives and the local population. In 1612 the rains are not attributable to the category of bad weather but, for the fragility of the paduan hydrographic network, they again contribute to the breakage of the banks. In 1627 at Este, in the lower paduan, the gravity of the situation pushes at the local level to try to understand the geographical connections of this liquid world because the waters of the upper vicentino influence those of the lower paduan.